Facilitating energy savings with programmable thermostats: evaluation and guidelines for the thermostat user interface - Peffer, Therese; Perry, Daniel; Pritoni, Marco; Aragon, Cecilia; Meier, Alan (Ergonomics, 2013)
Thermostats control heating and cooling in homes - representing a major part of domestic energy use - yet, poor ergonomics of these devices has thwarted efforts to reduce energy consumption. Theoretically, programmable thermostats can reduce energy by 5-15%, but in practice little to no savings compared to manual thermostats are found. Several studies have found that programmable thermostats are not installed properly, are generally misunderstood and have poor usability. After conducting a usability study of programmable thermostats, we reviewed several guidelines from ergonomics, general device usability, computer-human interfaces and building control sources. We analysed the characteristics of thermostats that enabled or hindered successfully completing tasks and in a timely manner. Subjects had higher success rates with thermostat displays with positive examples of guidelines, such as visibility of possible actions, consistency and standards, and feedback. We suggested other guidelines that seemed missing, such as navigation cues, clear hierarchy and simple decision paths. Practitioner Summary: Our evaluation of a usability test of five residential programmable thermostats led to the development of a comprehensive set of specific guidelines for thermostat design including visibility of possible actions, consistency, standards, simple decision paths and clear hierarchy. Improving the usability of thermostats may facilitate energy savings.